The effects and mechanisms of natural products on Helicobacter pylori eradication - Deng, Ruiyi; Chen, Xu; Zhao, Shiqing; Zhang, Qingying; Shi, Yanyan (Frontiers in Cellular and Infection Microbiology, 2024)
Helicobacter pylori (H. pylori) eradication is pivotal for alleviating gastric mucosal inflammation and preventing the progression of gastric diseases. While antibiotic-based therapies have achieved significant success in H. pylori eradication, challenges such as antibiotic resistance, drug toxicity, side effects, nonadherence, inapplicability, and disruption of gastrointestinal microflora have emerged. Updated therapies are urgently needed to suppress H. pylori. Nature has provided multitudinous therapeutic agents since ancient times. Natural products can be a potential therapy endowed with H. pylori eradication efficacy. We summarize the basic information, possible mechanisms, and the latest research progress of some representative natural products in H. pylori eradication, highlighting their safety, accessibility, efficiency, and ability to overcome limitations associated with antibiotic application. This review highlights the potential therapeutic advantages of incorporating ethnomedicine into anti-H. pylori regimens.The findings of this review may provide insights into the development of novel natural products and expand the therapeutic options available for H. pylori eradication.